2017
DOI: 10.1002/art.40229
|View full text |Cite
|
Sign up to set email alerts
|

Role of Stromelysin 2 (Matrix Metalloproteinase 10) as a Novel Mediator of Vascular Remodeling Underlying Pulmonary Hypertension Associated With Systemic Sclerosis

Abstract: Gene expression profiling of EPC-derived ECs identified MMP10 as a novel candidate gene in SSc-associated PH. MMP10 is overexpressed in the serum and pulmonary arteries of patients with SSc-associated PH, and its blockade alleviates PH in the Fra-2-Tg mouse model. MMP10 appears to be a prospective treatment target for this devastating disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…OPN has also been associated with IPAH (Lorenzen et al, 2011 ) and is therefore not specific for SSc-PAH. Circulating pro-MMP-10 was increased, in SSc-PH patients in comparison with SSc patients without PH or controls, which is consistent with MMP-10 overexpression in the pulmonary arteries of SSc-PAH patients (Avouac et al, 2017 ). The matrix metalloproteinase tissue inhibitor-4 (TIMP-4) may contribute to extracellular matrix deposition in SSc and its level is correlated with elevated SPAP in SSc patients (Gialafos et al, 2008 ).…”
Section: Extracellular Matrix Componentssupporting
confidence: 70%
“…OPN has also been associated with IPAH (Lorenzen et al, 2011 ) and is therefore not specific for SSc-PAH. Circulating pro-MMP-10 was increased, in SSc-PH patients in comparison with SSc patients without PH or controls, which is consistent with MMP-10 overexpression in the pulmonary arteries of SSc-PAH patients (Avouac et al, 2017 ). The matrix metalloproteinase tissue inhibitor-4 (TIMP-4) may contribute to extracellular matrix deposition in SSc and its level is correlated with elevated SPAP in SSc patients (Gialafos et al, 2008 ).…”
Section: Extracellular Matrix Componentssupporting
confidence: 70%
“…Current treatments can relieve some PAH symptoms and can slow the progress of PAH in some patients, but they have limited impact on the cellular and molecular mechanisms involved in pathogenic pulmonary vascular remodeling. Among them, it is now well known that the dynamic and unadapted remodeling of extracellular matrix (ECM) remodeling not only leads to qualitative and quantitative changes modulating vessel stiffness but also forms a permissive milieu influencing cell motility, proliferation, apoptosis, and differentiation (2)(3)(4)(5). Consistent with these notions, beneficial effects of different protease inhibitors have been reported in several animal models of pulmonary hypertension (PH) (6)(7)(8)(9)(10).…”
mentioning
confidence: 85%
“…On the contrary, it has been demonstrated that SSc dermal microvascular endothelial cells exhibit impaired expression of NRP-1 due to Fli1 deficiency, while SSc late-outgrowth EPC-derived endothelial cells have a genuine phenotype characterized by normal expression levels of either Fli1 or NRP-1 ( 77 ). In another study, gene expression profiling of EPC-derived endothelial cells identified matrix metalloproteinase 10 (MMP10) as a novel candidate gene in SSc-associated PH ( 79 ). MMP10 seems to have a predominant role in pathologic conditions related to tissue repair and inflammation ( 80 ) and more recently its role in neovascularization has also been proposed ( 81 , 82 ).…”
Section: Epcs In Sscmentioning
confidence: 99%
“…Circulating serum proMMP10 concentrations were markedly increased in patients with SSc-associated PH compared to SSc patients without PH and healthy controls. Microarray experiments showed that the MMP10 gene was the top upregulated gene in EPC-derived ECs from patients with SSc-associated PH ( 79 ).…”
Section: Epcs In Sscmentioning
confidence: 99%